Neoadjuvant SBRT combined with immunotherapy in NSCLC: from mechanisms to therapy - Shi, Yanhong; Ma, Xiaoyan; He, Dan; Dong, Bingwei; Qiao, Tianyun (Frontiers in Immunology, 2023)
The utilisation of neoadjuvant immunotherapy has demonstrated promising preliminary clinical outcomes for early-stage resectable non-small-cell lung cancer (NSCLC). Nevertheless, it is imperative to develop novel neoadjuvant combination therapy regimens incorporating immunotherapy to further enhance the proportion of patients who derive benefit. Recent studies have revealed that stereotactic body radiotherapy (SBRT) not only induces direct tumour cell death but also stimulates local and systemic antitumour immune responses. Numerous clinical trials have incorporated SBRT into immunotherapy for advanced NSCLC, revealing that this combination therapy effectively inhibits local tumour growth while simultaneously activating systemic antitumour immune responses. Consequently, the integration of SBRT with neoadjuvant immunotherapy has emerged as a promising strategy for treating resectable NSCLC, as it can enhance the systemic immune response to eradicate micrometastases and recurrent foci post-resection. This review aims to elucidate the potential mechanism of combination of SBRT and immunotherapy followed by surgery and identify optimal clinical treatment strategies. Initially, we delineate the interplay between SBRT and the local tumour immune microenvironment, as well as the systemic antitumour immune response. We subsequently introduce the preclinical foundation and preliminary clinical trials of neoadjuvant SBRT combined with immunotherapy for treating resectable NSCLC. Finally, we discussed the optimal dosage, schedule, and biomarkers for neoadjuvant combination therapy in its clinical application. In conclusion, the elucidation of potential mechanism of neoadjuvant SBRT combined immunotherapy not only offers a theoretical basis for ongoing clinical trials but also contributes to determining the most efficacious therapy scheme for future clinical application.